Seepage of contaminants from waste containment - Ismail, Z.; Hashim, Roslan (2006)
An alternative approach to assist the environmental engineer in his care for the geo-environment is described in the stochastic continuum modelling of seepage from waste facilities. The prediction of seepage can be conducted for typical soil and protective layers around the containment to investigate possible contaminant movement under steady state conditions. An important parameter controlling the transport of these contaminants is the hydraulic conductivity of the soil. This paper looks at afresh approach to the application of stochastic continuum modeling in generating hydraulic conductivity by kriged simulation. Flow and transport were computed numerically for the model. Results show that the approach is well suited for the simulation of seepage of contaminants around waste containment facilities.